Anatomical characteristics for cellulose production of reaction wood of inclined eucalypt trees - Boschetti, Walter Torezani Neto; Paes, Juarez Benigno; Oliveira, José Tarcísio da Silva; Dudecki, Larissa (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the anatomical characteristics for cellulose production of normal and reaction (tension and opposite) woods of the Eucalyptus grandis x Eucalyptus urophylla clone with inclined stem by the action of the wind. Trees were grouped into four grades of inclination, ranging from 0 to 50°. The anatomical characteristics of vessel elements and fibers were evaluated in the longitudinal direction of the stem, on the upper and lower sides of the inclination, on tension and opposite woods, respectively. The frequency and the tangential vessel diameter, as well as the fiber dimensions and their respective quality indices, were influenced by inclination. In tension and opposite woods, the vessels showed reduced diameter and increased frequency. A difference in fiber length between tension, opposite, and normal woods was observed, with influence on fiber quality indices. The high variability in the size of the fibers and vessels of reaction wood contributes to reduce the quality of the wood of the inclined stems for cellulosic pulp production.